Plastics and the Environment—Current Status and Challenges in Germany and Australia. Issue 18 (6th September 2020) - Wurm, Frederik R.; Spierling, Sebastian; Endres, Hans‐Josef; Barner, Leonie
Abstract: Polymers and plastics play a very important part in the modern world and contribute to people's wellbeing and comfort. However, products made of them are contributing to land‐ and marine‐based environmental pollution due to littering and other ways of emission, and therefore threaten ecosystems worldwide. However, waste management and responses by governments and the consumer differ strongly from country to country. The current article provides an overview of several important aspects of polymer waste and plastic pollution as well as describes selected strategies to mitigate these using examples from Germany and Australia, and therefore aims to contribute to the resolution of the ever‐increasing problem of unsustainable plastic consumption, disposal, and pollution. Abstract : Germany and Australia—in many aspects very different countries. Current challenges in plastic pollution and possible waste management strategies are highlighted using Germany and Australia as examples—geographically very different, but with a common ground on reducing, reusing, and recycling of plastics.